2011
DOI: 10.1186/1476-072x-10-18
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and the socioeconomic and built environment: geovisualization of disease prevalence and potential contextual associations using ring maps

Abstract: BackgroundEfforts to stem the diabetes epidemic in the United States and other countries must take into account a complex array of individual, social, economic, and built environmental factors. Increasingly, scientists use information visualization tools to "make sense" of large multivariate data sets. Recently, ring map visualization has been explored as a means of depicting spatially referenced, multivariate data in a single information graphic. A ring map shows multiple attribute data sets as separate rings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 32 publications
(42 reference statements)
0
31
0
Order By: Relevance
“…The ‘ring map’ is a relatively new technique, which allows factors of interest (such as putative environmental determinants) to be displayed circumferentially around a map 41. To produce these, we aggregated data to the level of middle super output area (n=31) and presented as quintiles of risk.…”
Section: Methodsmentioning
confidence: 99%
“…The ‘ring map’ is a relatively new technique, which allows factors of interest (such as putative environmental determinants) to be displayed circumferentially around a map 41. To produce these, we aggregated data to the level of middle super output area (n=31) and presented as quintiles of risk.…”
Section: Methodsmentioning
confidence: 99%
“…However, diabetes mellitus prevalence was not higher among Hispanics compared to Caucasians in both our crude and adjusted models. Whereas family income predicts diabetes mellitus prevalence among African Americans, similar claims could not be made of the Hispanics relative to Caucasians [7,[21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a wealth of studies on walkability and healthy food resources, most often in relation to obesity, with many, but not all, finding an inverse association (see Papas et al, 64 Booth et al, 65 and Feng et al 66 for reviews), and others found that inequalities in these features may explain inequalities in obesity. 67 Research into obesity-related outcomes including diabetes and cardiovascular disease have been speculated, 18,68 but the empiric literature has yielded mixed results, 12,21,22,66,[68][69][70][71] which may be owing to incomplete measurement of the built environment.…”
Section: The Built Environmentmentioning
confidence: 99%